THE AVAILABILITY OF MACROELEMENTS AND PRODUCTIVINI OF COWS AT DIFERENT LEVELS OF PROTEIN SUPPLY - Цвігун, А. Т.; Цвігун, О. А. (Podilian Bulletin: Agriculture, Engineering, Economics, 2016)
The availability of mineral elements studying is as important as the digestibility of organic compounds studying because they are used by the body from a ration not in 100%. The aim of the study was to investigate the availability of elements in I, II and III Phases of lactation and productivity of cows at different levels of protein supply. Research objectives include 4% milk yields study and the balance experiment study of visible availability of sulfur, phosphorus, chlorine, calcium, potassium, sodium, magnesium and sodium in different phases of lactation. Findings. 1. The highest 4% milk yield was in the third group of cows that received 20% of protein (18,46 kg) additionally into the ration, there wereslightly lower indicator in the second group of cows that received 10% of protein (17,38 kg) in addition compared to the control group (16,24 kg). As for the visible availability of macroelements, the results of the study indicate that in I, II and III Phases of lactation the visible availability of macroelements was the lowest in the control group. When you add to the ration 20% of protein the availability of phosphorus is increased by 2,7-5,33%, chlorine by 3,3-8,2; calcium by 3,34-5,42; and potassium by 1,7-5,43%. When you add to the ration 10% of protein only chlorine availability is significantly increased by 1,64-2,28%, as for other macroelements the control difference was not reliable. The visible availability of sulfur, phosphorus, chlorine, calcium, potassium, magnesium in rations of cows at different levels of protein supply in I, II and III phases of lactation is detailed studied. The received data on the availability of macroelements should be considered when balancing the rations.